A new case of false “wide” distribution for tropical cladocerans: the genus Notoalona Rajapaksa & Fernando, 1987 (Crustacea: Cladocera) in the Old World - Neretina, Anna N.; Kotov, Alexey A.; van Damme, Kay (Zootaxa, 2019)
Members of the genus Notoalona Rajapaksa & Fernando, 1987 (Cladocera: Chydoridae: Aloninae) are small-sized chydorids, inhabiting tropical water bodies around the World. Based on morphological features two species, N. globulosa (Daday, 1898) and N. pseudomacronyx Van Damme, Maiphae & Sa-Ardrit, 2013, were revealed in tropical Asia, but the status of African populations has remained unclear for a long time. Some authors identified African specimens as N. globulosa, others considered them as potentially new species awaiting description. Here we reexamined morphology of Notoalona populations from tropical Asia (Thailand, Laos) and Africa (Ethiopia, Kenya, Sudan and Madagascar). Although parthenogenetic females from Asia and Africa are basically similar, a single stable difference was found. In N. globulosa, the length of the basal spine and claw base are almost equal to each other, while in all investigated African specimens the basal spine is two times longer than base of postabdominal claw. This feature allows us to identify African populations as N. pseudomacronyx. Length of the setules in the basal group near the postabdominal basal spine, which was previously discussed in the literature as a specific feature for African populations, in fact, is overly variable and cannot be considered as diagnostic characteristic for the description of African populations as a separate taxon. Thus, the distribution range of N. pseudomacronyx is hereby expanded from South Africa to South East Asia, while N. globulosa s.l. occupies water bodies from tropical Asia to Australia. The same distribution patterns, when sibling species occur together in tropical Asia, have been shown for some other cladocerans as well. No doubt, the Asian tropics may be a particularly interesting area for future investigations on co-occurrence of sibling cladocerans, their ecology, behavior, genetics and potential hybridization.